Combating Drug Abuse among Students in Nigerian Tertiary Institutions: Prevention and Management Strategies - Isola, Oladotun Bamiji; Onigbinde, Moses Olukayode; David, Temitope Sarah; Akpati, Chibuzor Franklin (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Drug abuse is a trending global challenge among youths, especially those in tertiary institutions. Nigeria, having well above 1000 institutions comprising of universities, polytechnics and colleges of education, is not exempted from this menace. It is adduced by scholars that this current trend is caused by different factors such as peer pressure, poverty, lack of parental upbringing, unemployment and easy access to substances like alcohol, heroin, marijuana, and tramadol. This article highlights the urgent need for comprehensive strategies to tackle this multifaceted challenge, emphasizing the detrimental effects of substance misuse on academic performance, mental health, and social behavior. Despite government initiatives aimed at raising awareness and providing rehabilitation services, significant barriers like inadequate funding and limited mental health resources hinder effective intervention. The paper advocate for a holistic approach that involves various stakeholders-including educational institutions, families, community leaders, and religious organizations-to develop robust prevention programs. The article concludes that addressing drug abuse in Nigerian tertiary institutions requires a concerted effort to implement evidence-based strategies that mitigate immediate effects and foster long-term resilience among students. By prioritizing prevention and management initiatives, stakeholders can contribute to creating safer educational environments that enhance the well-being and academic success of Nigerian youth.